(3GdEOGQI GdUajI aj GdMdbI GdChdi ef GdJYdje GdCSGSj aj eOGQS HjQhJ (B: (3GdhGbY hGdeQJLis - (3jehJ, ShSfs ((3HjQhJs (3LGeYI GdbOjS jhSas, 2008)
(3gOaJ GdOQGSI GdMGdjI Edi eYQaI(B: 1) (3eG gh hGbY GdEOGQI GdUajI aj GdMdbI GdChdi ef GdJYdje GdCSGSj aj HjQhJ, (B2) (3eG gj CfeGW GdEOGQI GdUajI aj GdMdbI GdChdi ef GdJYdje GdCSGSj aj HjQhJ hJCKjQgG Ydi GdJdGejP, (B3) (3eG gj GdeDgdGJ GdTNUjI hGdegfjI ddeYde GdfGLM aj GdMdbI GdChdi ef GdJYdje GdCSGSj aj HjQhJ, (B4) (3eG gj TQhW GdEOGQI GdUajI aj GdMdbI GdChdi ef GdJYdje GdCSGSj aj HjQhJ, (B5) (3eG gj GdUYhHGJ GdJj bO JYJQV GdEOGQI GdUajI aj GdMdbI GdChdi ef GdJYdje GdCSGSj aj HjQhJ(B. (3EYJeOJ GdOQGSI GdMGdjI Ydi GdefgL GdhUaj GdJMdjdj, ddcTa Yf hGbY GdEOGQI GdUajI aj GdMdbI GdChdi ef GdJYdje GdCSGSj GdeYJeOI aj GdeOGQS eMhQ GdOQGSI, ceG Je JMVjQ GSJeGQI ehLgI Edi GdeYdejf cCOGI ddOQGSI(B. (3TedJ YjfI GdOQGSI YqOI eOGQS aj HjQhJ (B((3QSej, NGU, NGU eLGfj(B) (3aHdZ GdYOO GdELeGdj ddeOGQS (B31 (3eOQSI, (B11 (3QSejI, h(B17 (3NGUI(B. (3CeG HGdfSHI Edi YjfI GdeYdejf abO HdZ GdYOO GdELeGdj deYdej GdMdbI GdChdi ef GdJYdje GdCSGSj aj LejY eOGQS GdYjfI (B276(3; (B94 (3ef GdeOGQS GdQSejI, (B168 (3ef GdeOGQS GdNGUI h(B14 (3ef GdeOGQS GdNGUI GdeLGfjI(B. (3NdUJ GdOQGSI Edi eG jdj(B: 1) (3Ef GdfeW GdOcJGJhQj CcKQ MVhQkG eY GROjGO GdNHQI GdJYdjejI, (B2) (3RjGOI GdNHQI GdJYdjejI ddeYde aj GdMdbI GdChdi ef GdJYdje GdCSGSj JSGge aj bOQJg Ydi JMOjO GdeTGcd GdUajI heYGdLJgG, hJHjf Cf GdeYdejf jUHMhf CcKQ bOQI Ydi JMOjO fhY GdSdhc ZjQ GdeQZhH hcjajI JYOjd GdSdhc ZjQ GdeQZhH, hJYRjR GdSdhc GdeQZhH(B. 3) (3ZdHI GdfeW GdOcJGJhQj aj GdeOGQS GdQSejI hGdNGUI, HeYfi Cfg djS eMVhQkG HGdeOQSI GdQSejI abW, HGdebGHd JXgQ CfeGW CNQi ef GdEOGQI GdUajI (B((3GdfeW GdeJSGgd, hGdfeW GdeJPHPH(B) (3HTcd HGQR aj GdeOGQS GdQSejI(B. 4) (3jNJda CSdhH JMOjO GdeTGcd GdUajI heYGdLJgG aj GdMdbI GdChdi ef GdJYdje GdCSGSj aj HjQhJ HMSH fhY GdeOQSI HMjK JHOh CcKQ hVhMkG aj GdeOGQS GdNGUI ebGQfkI eY GdeOGQS GdQSejI hGdNGUI GdeLGfjI; hjYhO Pdc Edi WHjYI GdGNJdGa aj fhY GdeOGQS hGdXQha GdeMjWI aj cd eOQSI ef LgI hEdi Cf JMOjO gPg GdeTGcd jQJHW CjVkG HfhYjI GdeYde hNdajJg GdJQHhjI hGdeLJeYjI ef LgI KGfjI, hbO Jchf CjVkG ef LgI KGdKI Edi YOe hLhO GSJQGJjLjGJ NGUI YfO GdeOGQS dJMOjO gPG GdLGfH hJhVjMg HTcd Objb(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Class Management; Cycle primaire; Elementary Education; Gestion d$1 (Bune classes; (3GOGQI GdUas; (3GdeQMdI GdGHJOGFjIs